User Experience Evaluation of the Maxim Application using the HEART Metrics Method - Ningrum, Meriana Prihati; Megawati, Megawati; Saputra, Eki; Fronita, Mona; Anofrizen, Anofrizen (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The rapid growth of online transportation applications has led to increasing user expectations for efficient, intuitive, and reliable user experiences (UX). Maxim, as one of the emerging platforms in Indonesia, offers competitive pricing and wide service coverage, yet still faces challenges such as GPS inaccuracy, fare inconsistencies, and limitations with cashless payments. This study aims to evaluate the User Experience (UX) of the Maxim application in Pekanbaru using the HEART Metrics framework, which consists of five variables: Happiness, Engagement, Adoption, Retention, and Task Success. Data were collected through a Likert-scale questionnaire distributed to 100 respondents, with the sample size determined using the Lemeshow formula. The data were tested for validity and reliability, and analyzed using SPSS and Microsoft Excel. This study provides insight into user expectations and preferences as a foundation for service improvement. The results show that Happiness (73.8%), Adoption (72.4%), and Task Success (70.2%) are at a high level of usability, while Engagement (65.8%) and Retention (67.7%) did not meet the 70% usability benchmark. Overall, the Maxim application offers a good user experience, but improvements are needed in user engagement and retention through the addition of innovative features, GPS optimization, and enhanced service quality.